2007
DOI: 10.1038/sj.ejhg.5201968
|View full text |Cite
|
Sign up to set email alerts
|

Dissecting the molecular mechanisms in craniofrontonasal syndrome: differential mRNA expression of mutant EFNB1 and the cellular mosaic

Abstract: Craniofrontonasal syndrome (CFNS) is an X-linked malformation syndrome with variable phenotype that is caused by mutations in the ephrin-B1 gene (EFNB1). Over 50% of EFNB1 mutations result in premature termination codons that may elicit mRNA degradation by the nonsense-mediated decay pathway. To assess the effects of various mutations at the transcript level, expression of EFNB1 mRNA was studied by RT-PCR in fibroblast cultures established from CFNS female patients. Compared to the wild-type and two missense m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
1
3

Year Published

2008
2008
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(42 citation statements)
references
References 26 publications
0
38
1
3
Order By: Relevance
“…In the other two families, the clinical features differed highly, suggesting that intrafamilial variability can be significant. A genotype-phenotype correlation seems to be unlikely, based on this intrafamilial variability and a previous study, 26 and was not found in this study.…”
Section: Phenotype Of Craniofrontonasal Syndrome (Efnb1)contrasting
confidence: 79%
See 3 more Smart Citations
“…In the other two families, the clinical features differed highly, suggesting that intrafamilial variability can be significant. A genotype-phenotype correlation seems to be unlikely, based on this intrafamilial variability and a previous study, 26 and was not found in this study.…”
Section: Phenotype Of Craniofrontonasal Syndrome (Efnb1)contrasting
confidence: 79%
“…24,28 A genotype-phenotype correlation has not been proven, and previous studies suggest that this is unlikely. 26 Taken together, around 20% of the patients screened for CFNS did not display a mutation in the EFNB1 gene. 21,23,25 Multiple explanations have been proposed, one of which is misdiagnosis of some of the included patients.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…Nonsense and frameshift mutations in the efnb1 gene were reported to undergo NMD. 81 In fact these mutations are considered to be contributors to the pathogenic mechanisms reported in the human X-linked malformation syndrome, craniofrontonasal syndrome (CFNS). Therefore, accumulating evidence implicates mRNA stability as a possible regulatory or deregulatory process in Eph/ephrin expression in cancer and other pathologies.…”
Section: Post-transcriptional Regulationmentioning
confidence: 99%